Pengaruh Persepsi Intensitas Pelatihan Dan Persepsi Kesiapan Pada Pelaporan Keuangan Berdasarkan SAK EMKM - Andari, Atik Tri; Putranti, Eti; Setianingsih, Novie Astuti; Asmoro, Wiwiek Kusumaning (Universitas Gorontalo, 2024)
The quality of financial reports describes the performance of the business being run. Financial reporting by MSMEs uses SAK EMKM, so intensive training and readiness is required in preparing financial reports. This research aims to analyze perceptions of training intensity and perceptions of readiness in preparing financial reports based on SAK EMKM. The MSMEs in question are MSMEs in the manufacturing industry in Kediri City. This research uses a questionnaire distributed to MSME owners. This research uses multiple linear regression with the SPSS application. The results of this research indicate that perceptions of training intensity and perceptions of readiness influence the preparation of financial reporting based on SAK EMKM.